Concurrent amyotrophic lateral sclerosis and cystic fibrosis supports common pathways of pathogenesis. Issue 5 (September 2013) - Lo, Christine; Cooper-Knock, Johnathan; Garrard, Kate; Martindale, Joanne; Williams, Timothy; Shaw, Pamela
Abstract: We present a case of concurrent cystic fibrosis (CF) and amyotrophic lateral sclerosis (ALS). To our knowledge this is the first reported coincidence of these two diseases. Although TDP-43 dysfunction has been linked to both pathologies, it does not appear to be pivotal in this individual who does not display TDP-43 mediated aberrant splicing of the CFTR gene or carry a mutation in the TARDBP gene. Alternative reasons for the coincidence are discussed including medication, infection, hypoxia and loss of function of the CFTR channel. Our findings await validation by others, but as the prognosis of CF improves then clinicians in both fields should be aware of the possibilities highlighted by this case.